Aplikasi Beberapa Jenis Pupuk Organik Kemasan untuk Menekan Penyakit Akar Gada dan Meningkatkan Pertumbuhan Tanaman Kubis (Brassica oleracea L.) - DEWI, NI MADE PRITIYANTI; SUDANA, I MADE; SUWASTIKA, A. A. NGURAH GEDE; SUADA, I KETUT (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.7, No.1, Januari 2018, 2018)
Application Some Types of Organic Fertilizer in a Pack To Suppress Clubroots and Improve Cabbage (Brassica oleracea L.) Plant Growth Cabbage is one type of leaf vegetables from subtropics area that has been known for a long time and cultivated in Indonesia. One of the hardest cabbage diseases is clubroots caused by the Plasmodiophora brassicae pathogen. This pathogen can cause high damage to cabbage plants. The used of synthetic pesticides is less success in the implementation, and caused environmental pollution, especially the soil, this study tried to control clubroots in the cabbage by using 8 types of organic fertilizer in a pack. This study used a Completely Randomized Design (CRD) with 9 treatments including controls with three replications. The results obtained four best treatments that were effective in suppressing clubroots while increasing the leaf height, leaf amount, leaf area, and maximum dry weight of the plants, that three best treatments were organic fertilizer PSBN, Multitonik, and Biotonik. The best treatment to suppress clubroots is found in organic fertilizer PSBN, Multitonik, and Biotonik which has the lowest percentage of ulcer attack by 33,33-55,56% compared to control (100%).